Staff Development Programme for Primary Education Teachers in Nigeria: Challenges and Ways Forwards - Ogunode Niyi Jacob; Adah Samuel; Audu Elizabeth I; Wama Pajo (International Journal of Marketing & Human Resource Research, 2020)
The article discussed the challenges facing the staff development programme for primary school teachers in Nigeria. Secondary data was used to support the points raised in the article. The secondary data were sourced from print material and online publication by recognized institutions and individual author. There are many challenges facing the staff development programme for primary school teachers in Nigeria. Some of the challenges include; inadequate funding, lack of strategic plans, poor implementation of staff development policies, institutional corruption, poor internal school administration of staff development programme for teachers, unstable educational policies, political instability and lack of data/information on training need gaps of schools. To solve these challenges, it was recommended that: the government should embark on need training assessment of basic schools, develop an action plans, develop a financial plan for implementation, set up effective monitoring and evaluation system, ensure policies continuity and fight all institutional corruption in the ministries.